DETECTION OF OCHRATOXIN A IN INSTANT COFFEE BY UPLC-MS/MS - MINCEA, Manuela; IONAȘCU, Cosmin; KIS, Katalin; OSTAFE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2016)
A rapid, accurate and economic procedure has been applied to extract and analyze trace level of ochratoxin A (OTA) in instant coffee. The OTA was extracted and cleaned-up by methanol extraction followed by retention on IRA-400 anion exchanger and quantified by Ultra Performance Liquid Chromatography (UPLC) with MS/MS detection. Under optimum conditions, the detection limit (S/N = 3) was 0.05 ng/g and recoveries of OTA at spiking levels of 5, 10, and 20 ng/mL, were 82.67 ± 8.05%, 96.87 ± 4.63%, and 98.25 ± 4.46% respectively.